Postnatal Development of Pancreas in Non-Descript Pigs - Gross Anatomical Study - Shanthini S; Rajathi S; S, Muthukrishnan; Ninu A.R (Indian Journal of Veterinary Anatomy, 2026)
The present research aimed to study the gross anatomy of pancreas in postnatal age groups of non–descript pigs. Pancreas in pig was located in the dorsal part of the abdominal cavity intimately related to the proximal part of the duodenum. Six pancreases were collected from each of three different age groups of pigs from the nearby slaughter houses. The pancreas of pigs appeared lobulated and triangular in shape. It was pale yellow, in neonatal group and yellowish cream colour, in young and adult ages. It was soft to touch during postnatal ages. The pancreas of pig was observed with three lobes namely splenic lobe, duodenal lobe, and connecting lobe. Splenic lobe was the largest and formed not only one side of the triangle but also extended from the corresponding angle of the triangle. Duodenal lobe was associated with the duodenum. Connecting lobe was the smallest lobe. Two main ducts were observed; one as main pancreatic duct and the other as accessory pancreatic duct. The accessory pancreatic duct was found to be draining the pancreatic secretions of splenic lobe and the cranial part of duodenal lobe. It opened to the cranial part of duodenum and its opening was in the same level but opposite to the bile duct opening in all the postnatal ages studied. The main pancreatic duct was found to be draining the pancreatic secretions from the caudal part of duodenal lobe, connecting lobe and bridge and opened at further caudal part of the duodenum.